ISSUES OF FIRE PREVENTION OF ELECTRICAL EQUIPMENT IN RESIDENTIAL AND PUBLIC BUILDINGS - Anton A. Nazarov; Alexey I. Ryabikov; Gennady V. Bokov; Olga I. Gruzinova (Актуальные вопросы пожарной безопасности)
There are presented the results of analysis of methods for fire prevention of electrical equipment of the electrical part of residential and public buildings. There are shown the advantages and disadvantages. The use of technical means for diagnosing the condition of electrical equipment elements in terms of fire-hazardous manifestations is proposed. It is emphasized that the most effective and promising method of monitoring the state of fire safety of electrical equipment may be the use of thermal imaging and pyrometric means of continuous monitoring of electrical equipment elements.